Tax Strategy to Encourage MSME Growth: Analysis of Effectiveness and Constraints - Mutahira Nur Insirat; Nur Sandi Marsuni (Yayasan Amerta Insan Unggul, 2022)
Background: The COVID-19 pandemic significantly impacted Indonesia's economic growth, particularly affecting Micro, Small, and Medium Enterprises (MSMEs), which contributed significantly to the national GDP and non-oil exports. The prolonged enforcement of community activity restrictions (PPKM) limited physical sales channels, pushing MSMEs towards online platforms, albeit with varying success due to limited digital business knowledge among MSME owners. Objective: This study aims to analyze the effectiveness of tax incentives in sustaining MSME businesses during the pandemic and evaluate the challenges faced by MSMEs in using these incentives. Method: A qualitative descriptive approach using literature review was employed. Data sources include scholarly articles, government publications, and reports from relevant institutions such as the Ministry of Cooperatives and SMEs and the National Development Planning Agency (Bappenas). Results: Tax incentives, including reduced rates of Value Added Tax (VAT) and Income Tax (PPh), were introduced by the government to alleviate the financial burden on MSMEs and stimulate economic recovery. However, the effectiveness varies due to limited understanding and awareness among MSME owners about tax regulations and incentives. Many MSMEs struggled to meet the eligibility criteria or faced challenges in accessing the benefits. Conclusion: Despite government efforts to support MSMEs through tax incentives during the pandemic, significant barriers such as lack of awareness, complex eligibility requirements, and inadequate dissemination of information hindered their effective utilization. Continuous efforts are needed to increase awareness, simplify procedures, and ensure equitable access to tax incentives for sustainable MSME development.